The Rac1 regulator ELMO1 controls vascular morphogenesis in zebrafish - Epting, Daniel; Wendik, Björn; Bennewitz, Katrin; Dietz, Christian; Driever, Wolfgang; Kroll, Jens (Circulation research, 2010)
Rationale: Angiogenesis is regulated by the small GTPase Rac1. The ELMO1/DOCK180 complex forms a guanine nucleotide exchange factor for Rac1, regulating its activation during cell migration in different biological systems. - Objective: To investigate the function of ELMO1/DOCK180 in vascular development. - Methods and Results: In situ hybridization studies for elmo1 identified a vascular and neuronal expression in zebrafish. Morpholino-based expression silencing of elmo1 severely impaired the formation of the vasculature, including intersomitic vessels, the dorsal longitudinal anastomotic vessel, the parachordal vessel, and the development of the thoracic duct in tg(fli1:EGFP) embryos. Mechanistically, we identified Netrin-1 and its receptor Unc5B as upstream activators of the ELMO1/DOCK180 complex, regulating its functional interaction and leading to Rac1 activation in endothelial cells and vessel formation in zebrafish. - Conclusions: Our data have identified a novel signaling cascade regulating vasculature formation in zebrafish